Differential Gene Expression Changes in Children with Severe Dengue Virus Infections - de Kruif, Martijn D.; Setiati, Tatty E.; Mairuhu, Albertus T. A.; Koraka, Penelopie; Aberson, Hella A.; Spek, C. Arnold; Osterhaus, Albert D. M. E.; Reitsma, Pieter H.; Brandjes, Dees P. M.; Soemantri, Augustinus; van Gorp, Eric C. M. (PLOS Neglected Tropical Diseases, 2008)
Author SummaryDengue virus infection is an impressively emerging disease that can be fatal in severe cases. It is not precisely clear why some patients progress to severe disease whereas most patients only suffer from a mild infection. In severe disease, a “cytokine storm” is induced, which indicates the release of a great number of inflammatory mediators (“cytokines”). Evidence suggested that a balance could be involved between protective and pathologic cytokine release patterns. We studied this concept in a cohort of Indonesian children with severe dengue disease using a gene expression profiling method.The study showed that the immune response to severe dengue infection was characterized by up-regulation of interferon pathway–associated cytokines and down-regulation of nuclear factor (NF)-kappaB pathway–associated cytokines. Many of the NF-kappaB pathway–related genes, but not the interferon pathway–associated genes, correlated with adverse clinical events such as development of pleural effusion and hemorrhagic manifestations. In addition, the study showed that the expression of specific pathogen recognition receptors called Toll-like receptors was differentially regulated in patients with dengue. Together, the data show that different immunological pathways may indeed be differently expressed and associated with different clinical outcomes in children with severe dengue infections.